BAURAN PROMOSI DALAM MENINGKATKAN PENJUALAN SEPEDA MOTOR HONDA: STUDI KASUS DEALER PT TRIO MOTOR MARTADINATA - Rika Sylvia; Hairunnisa Hairunnisa (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2024)
This study aims to analyze the effectiveness of the promotional mix in increasing Honda motorcycle sales at PT. Trio Motor Martadinata. The promotional mix comprises five main elements: advertising, sales promotion, personal selling, public relations, and direct marketing. The research method used is quantitative descriptive with a sample of 111 respondents who are dealer customers. The results of the study indicate that all elements of the promotional mix have a significant influence on consumer purchasing decisions. In particular, advertising and sales promotion have proven effective in attracting consumer attention, while personal selling also contributes positively to purchasing decisions. However, public relations and direct marketing activities need to be improved to strengthen the company's image and consumer engagement. Thus, this study recommends that PT. Trio Motor Martadinata strengthens existing promotional strategies, improves training for sales staff, and is more active in social activities and utilizing digital media to achieve better marketing goals.